The usage of a modified straight-leg raise neurodynamic test and hamstring flexibility for diagnosis of non-specific low back pain: A cross-sectional study - Hermosura, Joan; Lohman, Everett; Bartnik-Olson, Brenda; Venezia, Jonathan; Daher, Noha (PloS one, 2024)
The main purpose of this research study was to compare mean modified straight-leg raise test (mSLR) and hamstring muscle length (HL) between chronic non-specific low back pain (LBP) and healthy subjects to understand the possibility of neuropathic causes in LBP population as it may impact the diagnosis and treatment of LBP. Another purpose was to compare mean mSLR between those with lumbar nerve root impingement and those without as determine by magnetic resonance imaging (MRI). The design of the study is cross sectional and included 32 subjects with ages ranging from 18-50 years old. Clinical exam objective measures were collected such as patient questionnaires, somatosensory tests, HL range of motion, and a mSLR test, and were compared to the findings from a structural lumbar spine MRI. There were no significant differences in mean HL angulation and mSLR angulation between LBP and healthy subjects (p>0.05). There was no significant difference in mean HL by impingement by versus no impingement (38.3±15.6 versus 44.8±9.4, p = 0.08, Cohen's d = 0.50). On the other hand, there was a significant difference in mean mSLR angulation by impingement (57.6.3±8.7 versus 63.8±11.6, p = 0.05, Cohen's d = 0.60). The mSLR test was found to be associated with lumbar nerve root compression, regardless of the existence of radiating leg symptoms, and showed no association solely with the report of LBP. The findings highlight the diagnostic dilemma facing clinicians in patients with chronic nonspecific LBP with uncorrelated neuroanatomical image findings. Clinically, it may be necessary to reevaluate the common practice of exclusively using the mSLR test for patients with leg symptoms. This study may impact the way chronic LBP and neuropathic symptoms are diagnosed, potentially improving treatment methods, reducing persistent symptoms, and ultimately improving disabling effects.